The spatial impact of new urbanization construction on total factor productivity in China - Wang, Yuanyuan; Li, Shengsheng (Asian Journal of Economics and Empirical Research, 2025)
This study examines the spatial impact of new urbanization on total factor productivity (TFP) in China using data from 199 prefecture-level cities from 2011 to 2019. We measured the level of new urbanization using an indicator system and the entropy weight method, and assessed TFP using the stochastic frontier production function model. The spatial Durbin model was employed to analyze the spatial effects empirically. The study found that (1) new urbanization has a positive spatial effect on TFP, and there is a spatial spillover effect. (2) The spatial effect of new urbanization on TFP has obvious city-level heterogeneity and regional heterogeneity. (3) The spatial spillover effect of new urbanization on TFP is most significant in second-tier cities and third-tier and lower cities. There is a "diffusion effect" of the spatial effect of the central and western cities on the neighboring areas, and a "siphon effect" of the spatial effect of the eastern cities, but both of these spatial effects are not significant. The spatial spillover effect of new urbanization on TFP in non-provincial capitals is significant, whereas the spatial effect in non-provincial capitals is not significant. These findings highlight the importance of considering regional context in urbanization policies to enhance TFP.